2008
DOI: 10.1136/hrt.2006.104745
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular size and function assessed by cardiac MRI predict major adverse clinical outcomes late after tetralogy of Fallot repair

Abstract: In this cohort, severe RV dilatation and either LV or RV dysfunction assessed by CMR predicted major adverse clinical events. This information may guide risk stratification and therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
238
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 451 publications
(256 citation statements)
references
References 29 publications
14
238
0
4
Order By: Relevance
“…12,14,23 In addition to volumes, CMR can also provide additional data on ejection fraction of both the RV and LV. In a cross-sectional study, Knauth et al 24 examined 88 patients with repaired TOF by CMR. Median time between TOF repair and enrollment in the study was 20.7 years, and median follow-up was 4.2 years.…”
Section: Cardiac Magnetic Resonance Measurements As An Indication Formentioning
confidence: 99%
See 2 more Smart Citations
“…12,14,23 In addition to volumes, CMR can also provide additional data on ejection fraction of both the RV and LV. In a cross-sectional study, Knauth et al 24 examined 88 patients with repaired TOF by CMR. Median time between TOF repair and enrollment in the study was 20.7 years, and median follow-up was 4.2 years.…”
Section: Cardiac Magnetic Resonance Measurements As An Indication Formentioning
confidence: 99%
“…28 Of course, LV function is an important predictor of outcome and, in the study by Knauth and colleagues mentioned above, diminished LV ejection fraction was as strong a predictor of adverse events as RV dysfunction. 24 Therefore, among patients with severe PR and diminished RV function, the addition of LV dysfunction would be an additional indication for PVR.…”
Section: Cardiac Magnetic Resonance Measurements As An Indication Formentioning
confidence: 99%
See 1 more Smart Citation
“…This allows serial follow-up of biventricular function. Knauth et al showed that severe right ventricular dilatation and either left or right ventricular dysfunction assessed by CMR predicted major adverse clinical events [25].…”
mentioning
confidence: 99%
“…Following surgical correction, many patients have moderate to severe pulmonary insufficiency (PI) with minimal or no residual pulmonary stenosis (PS). Chronic PI plays a pivotal role in right ventricular (RV) dilatation and dysfunction, following surgical repair of RV outflow tract (RVOT) obstruction (2)(3)(4)(5)(6)(7)(8). Most patients following surgical correction of TOF experience a prolonged asymptomatic phase.…”
Section: Introductionmentioning
confidence: 99%